2023
DOI: 10.3847/2041-8213/acbcd1
|View full text |Cite
|
Sign up to set email alerts
|

GRB 221009A: Discovery of an Exceptionally Rare Nearby and Energetic Gamma-Ray Burst

Abstract: We report the discovery of the unusually bright long-duration gamma-ray burst (GRB), GRB 221009A, as observed by the Neil Gehrels Swift Observatory (Swift), Monitor of All-sky X-ray Image, and Neutron Star Interior Composition Explorer Mission. This energetic GRB was located relatively nearby (z = 0.151), allowing for sustained observations of the afterglow. The large X-ray luminosity and low Galactic latitude (b = 4.°3) make GRB 221009A a powerful probe of dust in the Milky Way. Using echo tomography, we map … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 65 publications
(78 reference statements)
9
56
1
Order By: Relevance
“…The fitting result is shown in Figure 1. Currently, some works present results of the extinction values of GRB 221009A and find some significant influence from the host galaxy (e.g., Kann et al 2023;Levan et al 2023;Williams et al 2023). Our results may differ owing to the lack of UV band in the data we used, due to the broken power-law spectral index differing from the prediction based on the synchrotron radiation mechanism.…”
Section: Joint Spectral Analysis Of X-ray and Optical Bandmentioning
confidence: 50%
“…The fitting result is shown in Figure 1. Currently, some works present results of the extinction values of GRB 221009A and find some significant influence from the host galaxy (e.g., Kann et al 2023;Levan et al 2023;Williams et al 2023). Our results may differ owing to the lack of UV band in the data we used, due to the broken power-law spectral index differing from the prediction based on the synchrotron radiation mechanism.…”
Section: Joint Spectral Analysis Of X-ray and Optical Bandmentioning
confidence: 50%
“…The optical detection was somewhat remarkable, as the transient lies in the Galactic plane, and extinction along the line of sight is very high, E (B−V ) = 1.32 mag/A V = 4.1 mag (Schlafly & Finkbeiner 2011, hereafter SF11). It was furthermore reported that the source was also detected more than 10 minutes earlier by the Gas Slit Camera of the MAXI X-ray detector on board the International Space Station (Negoro et al 2022;Kobayashi et al 2022;Williams et al 2023). Overall, this is in agreement with a new Galactic transient.…”
Section: Introductionmentioning
confidence: 54%
“…The isotropic energy from this event is still to be confirmed, but initial estimates suggest it is E iso ∼ 1-6 × 10 54 [95,97,102,103], close to that of GRB 160625B [102]. Since Swift/BAT triggered on the afterglow emission (the first time in 18 years) rather than the prompt gamma-ray emission, Swift/UVOT observations only began an hour after the Fermi trigger [104]. In addition, due to the GRB's closeness to the Galactic plane, the optical/UV emission is affected by significant galactic extinction (A v 4 mag increasing in the UV to an A uvw2 10 mag).…”
Section: Record-breaking Grbsmentioning
confidence: 93%
“…Given these restrictions, GRB 221009A was still detected in the initial Swift/UVOT v image at 16.6 mag, and marginally detected in uvw1. Such a nearby and bright event is only expected once in 1000 years [104]. The results of the detailed analysis of this GRB are starting to be published; see [91,.…”
Section: Record-breaking Grbsmentioning
confidence: 99%